How reading comprehension is embodied and why that matters - Arthur M. GLENBERG (International Electronic Journal of Elementary Education, 2011)
Reading comprehension, much like comprehension of situations and comprehension of oral language, is embodied. In all cases, comprehension is the ability to take effective action on the basis ofaffordances related to the body, the physical world, and personal goals and cultural norms. In language contexts, action-based comprehension arises from simulating the linguistic content usingneural and bodily systems of perception, action, and emotion. Within this framework, a new approach to teaching reading comprehension is described: Teach children how to simulate while reading. TheMoved by Reading intervention teaches simulation in two stages. In the first stage, physical manipulation, children manipulate toys to simulate the content of what they are reading. After success in physically manipulating the toys, the children are taught to manipulate the toys in imagination. Research demonstrates that both physical and imagined manipulation leads to large gains in memory and comprehension.